Prevalence and clinical features of cryoglobulinaemia in multitransfused β-thalassaemia patients. Issue 11 (1st November 1999) - Perniola, R; De Rinaldis, C; Accogli, E; Lobreglio, G
Abstract : OBJECTIVE: The aim of the study was to determine the prevalence of cryoglobulinaemia and its clinical features among β-thalassaemia patients. METHODS: Eighty eight multitransfused β-thalassaemia patients were studied. They were physically examined and asked about the presence of cryoglobulinaemia related symptoms. Hepatitis C virus (HCV) serology, HCV-RNA, HCV subtypes, viraemia, serum ferritin, liver and kidney function tests, rheumatoid factor (RF), circulating immune complexes (CIC), complement levels and autoantibodies were all evaluated. The patients were divided into four groups: HCV-RNA positive patients with and without cryoglobulinaemia (groups A and B), HCV-Ab positive/HCV-RNA negative patients (group C), HCV-Ab negative patients (group D). RESULTS: Cryoglobulinaemia was present in 35 of 53 (66.0%) patients with chronic HCV infection. They had higher viraemia than non-cryoglobulinaemic viral carriers, but no statistical difference relating to sex or HCV subtypes was found. In comparison with the other groups, group A patients were older, had undergone transfusion therapy for a longer period, had received a higher number of transfusions, and had increased levels of RF and CIC, as well as consumption of C4; in addition, they had a higher prevalence of cirrhosis. Cutaneous lesions (purpura, Raynaud's phenomenon, nodules and leg rash), peripheral neuropathy and sicca syndrome symptoms were present only in group A. Musculoskeletal symptoms (bone pain, arthralgia and myalgia), weakness, splenomegaly, lymphadenopathy, skin ulcers and proteinuria were also commoner in group A, but the difference did not reach statistical significance, possibly because of partial overlap between cryoglobulinaemia and β-thalassaemia syndromes. CONCLUSION: Because of its high prevalence in multitransfused β-thalassaemia patients, cryoglobulinaemia needs to be systematically studied and considered in the differential diagnosis of various β-thalassaemia manifestations.